Global Market Penetration : Analysis On Malaysian Food & Beverage Manufacturing Industry's Product Competitiveness - Mohd Mandak, Noorasikin (2002)
The purpose of this study are to know the level of competitiveness of Malaysian food industry in managing their product policy as a strategy , as well as to suggest some guidelines and recommendations on the import elements of product policy in local food manufacturing industry's decision to penetrate global market.